Influence of taylor's and fayol'spostulates on the development of modern management techniques - Guerrero Agámez, Sergio Manuel; Canabal Gùzman, Javier Dario; Muñoz Hernandez, Helmer (Universidad Francisco de Paula Santander, 2015)
The managementprinciples proposed by Taylor and Fayol, despite having been postulatedmore than sixty yearsago, are so representative that they still prevail and remain valid to the point that modern organizations, regardless of the activity they develop, apply the principles as a rule thatallows them to implementthe proposed objectives and goals set forcontinuousquality improvement, quality management and quality assurance framed in a consistent cycle of planning, organizing, integrating, directing and controlling,and in the best case, reengineering processes. Although it is considered a topic that too much has been writtenabout, or otherwise by characterizingauthors of an extremely ancient context to what a modern administrationcan be, it is essential to make approximations that allow to recognize the past before modern processes. This paperpretends from the found results, to defendthe role of the classic postulates and in this same sense,to look for a connection bridge that will serve for future entrepreneurs in the organizational and managementconsolidation of their entities in pursuitof management consolidation.